Ritual Upacara Sri Tumpuk Di Pura Luhur Batukau Desa Pakraman Wongaya Gede Kabupaten Tabanan (1998-2022) - Ni Nyoman Buddhidewi Dharmakirti; Ida Bagus Gde Putra; Anak Agung Inten Asmariati (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2024)
This research discusses the Sri Tumpuk Ceremony at Pura Luhur Batukau Pakraman Wongaya Gede Village, Tabanan Regency (1998-2022). Balinese culture is very rich and numerous, ranging from the traditional culture owned by each resident in Bali, the religion practiced, the arts owned, the typical food owned by the Balinese region, Balinese traditional houses, Balinese traditional clothes, and places to worship in the Balinese region. One of these temple buildings that will be designated as cultural heritage and become a heritage of Balinese life, namely Pura Luhur Batukau. The formulation of the problem examined. First, Related to the Procession of the Sri Tumpuk Ceremony; Second, About the Meaning of the Sri Tumpuk Ceremony; Third, About the Implications of the Sri Tumpuk Ceremony. The purpose of the research in general, to find out the Culture, Tradition, History and Sincerity of doing Yadňya, which is related to the Sri Tumpuk Ceremony at Pura Luhur Batukau. The method used is Descriptive Qualitative Research Method. Data collection techniques with. First, Observation; Second, Interview; Third, Document; and Fourth, Library. The results of the research will discuss several related matters, namely: First, Related to the Procession of Sri Tumpuk Ceremony; Second, About the Meaning of Sri Tumpuk Ceremony; Third, About the Implications of Sri Tumpuk Ceremony.